A STUDY OF THE IMPACT OF ONLINE EDUCATION ON THE LEARNING AND PERSONALITY OF SECONDARY LEVEL STUDENTS - Swarnkar, Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the presented research study by researcher in “Study of the impact of online education on the Learning and personality of secondary level students”,The reseatcjer has studied the impact of online eduction on the Learning and personality of the students. In this research a significant difference has been found in the learning of the students of government and private institution In this study correlation has been found in Learning and personality of the students studing in government and private schools.